Avaliação da práxis em crianças menores de 3 anos sob a perspectiva da abordagem de integração sensorial de Ayres - Silva, Kátia Cezário da (2024)
The brain continuously receives and assimilates an uncountable number of sensory sensations from different organs of the body, producing motor and behavioral responses, so that a child can move and learn and thus behave in a productive and functional way. In this way, detecting and modulating sensory information from one's own body and the environment makes it possible to respond to the demands of everyday life (Ayres, 1972, 2004). However, when this process does not occur harmoniously, dysfunction in Sensory Integration is triggered. Ayres (1972, 2011) studied praxis difficulties and demonstrated how sensory dysfunctions can affect functional abilities, with praxis being a neurological process between cognition and motor action, while planning is the intermediate process that unites ideation with motor execution to allow adaptive interactions with the world (Ayres, 1972; Cermak; May-Benson, 2020). Ayres developed the Sensory Integration and Praxis Test (SIPT) to evaluate and diagnose children aged 4 to 8 years and 11 months with these difficulties (Ayres, 1989; Lane; Bundy; Gorman, 2020). Although the development of praxis in Sensory Integration in early childhood was little studied by Ayres, since then, instruments have been developed to evaluate sensory dysfunctions. However, little research has been carried out with few assessment instruments to understand and diagnose the praxis of babies and young children. Objective: Identify in the literature praxis assessment instruments from the perspective of Sensory Integration for children aged 0 - 12 years and categorize the domains, adapt them, and create a new instrument that makes it possible to evaluate the praxis of children under 3 years of age. Method: This is a methodological research with a quantitative approach for the construction and elaboration of an evaluation instrument. Methodological studies are those that aim to develop new instruments, create protocols, in addition to translating, validating and adapting pre-existing instruments (Swan et al., 2023). According to the COSMIN guidelines, the process of creating an instrument has ten steps and this research will focus on the first 5 phases. In phase 1, a scoping review was carried out to verify the existence of instruments that assess children's praxis. In phases 2 and 3, the psychometric rigor of the instruments found was reviewed and analyzed. In phase 4 the “construct” is described and, finally, in phase 5, the domains and items of each instrument were studied. Results: In the literature review, 8,161 articles were found and, after the inclusion criteria, a total of 95 articles were analyzed. 36 assessment instruments were found, of which 14 assess praxis, none of which directly assess praxis in the age range from birth to 1 year and 5 months. Of the 14 instruments that include items that evaluate praxis, only 10 instruments were found that studied domains and items, these were organized into 2 categories: direct measurement assessments and indirect measurement assessments. Conclusions: A direct measurement instrument was not found to evaluate children aged 0 to 36 months and the need to understand the markers in the development of praxis was perceived in order to evaluate these children earlier. It is clear that, to delve deeper into this age group, the study of Sensory Integration will need to be in-depth and correlated to cognition, as the praxis of ideation, planning and sequencing are dependent on these integrated and coordinated processes. It will also be necessary to delve deeper into motor markers, as they all simultaneously act to support the evaluation of these children's praxis.